(untitled) (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2006)
An experiment on the effectiveness of biopesticide made of ramayana (Cassia spectabilis) and tobacco leaves (Nicotiana tabacum) it called as Casnic, on Hypothenemus hampeiand Planococcus citriand its effect on the arthropods population fauna in coffee plantation had been conducted in Pest Laboratory of Indonesian Coffee and Cocoa Researh Institute and Bangelan Plantation in Malang. The treatment consisted of three level concentrations of botanical pesticide(15 ml, 30 ml, and 60 ml/lof water), Beauveria bassiana(at a dose 100 g spore per ha), metidation spraying (2 ml formulation per litre of water) and two control treatments (with and without soap). The field experiment was arranged in randomized complete block design (RCBD) with four replications. The results showed that botanical pesticide at the concentration of 30.0 ml stock solution per litre of water and applied four times with monthly interval was effective in controlling coffee berry borer (Hypothenemus hampei) and coffee mealy bug (Planococcus citri). The effectiveness was not significantly different compared to metidation and Beauveria bassianaat the dose of 0.8 l and 100 g formulation per ha per application. Application of the botanical pesticide did not show negative effect on the usefull predatory insects and other arthropods population in coffee ecosystem. Key words : Botanical pesticide, Cassia spectabilis, Nicotiana tabacum, Coffee, Hypothenemus hampei, Planococcus citri, Arthropods.